Tool design and parameter optimization for incremental sheet-forming process - Moayedfar, Majid (2013)
Incremental Sheet Forming (ISF) is a method developed to form a desired surface feature on sheet metals in batch production series. Due to lack of reliable data about the process, researchers are currently experimenting with the parameters to achieve the optimum process setting. In this work, ISF was carried out on stainless steel sheets using Computer Numerical Control (CNC) lathe and milling machines. Experiments were conducted to find out how the ISF process parameters i.e. tool material, spindle speed and feed rate, affect the quality of the part produced. Prior to running the experiments, a ball-point shaped tool made of bronze alloy was fabricated due to its superior ability to reduce the amount of friction and improve the surface quality of the stainless steel sheet compare to the aluminum-bronze and brass alloy. The experiments employed the method of forming in negative direction with a blank mold and the tool that helped to shape the desired part quickly. The differences between the milling and lathe machine were also considered in this study and the results showed that the lathe machine was more efficient in terms of programming and the working time was reduced by 50% for circular parts. The programming was generated using the MasterCAM software for the CNC lathe machine and edited before transferring to the machine. However, the programming for the milling machine was written manually for simplicity. The amount of lubrication was also one the parameters of interest in this study but its effect on the part output was not significant, therefore, the amount used was kept constant about 250 CC throughout the experiments to avoid waste of lubricant. Besides that, the temperature of the contact area was measured and it showed that the amount never rose to more than 80°C which was still acceptable for ISF. From the results, the optimum spindle speed was found to be at 186 rpm and the optimum feed rate was 500 m/min.